2010
DOI: 10.1115/1.4001192
|View full text |Cite
|
Sign up to set email alerts
|

An Accelerated 3D Navier–Stokes Solver for Flows in Turbomachines

Abstract: A new three-dimensional Navier–Stokes solver for flows in turbomachines has been developed. The new solver is based on the latest version of the Denton codes but has been implemented to run on graphics processing units (GPUs) instead of the traditional central processing unit. The change in processor enables an order-of-magnitude reduction in run-time due to the higher performance of the GPU. The scaling results for a 16 node GPU cluster are also presented, showing almost linear scaling for typical turbomachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(40 citation statements)
references
References 13 publications
0
39
0
1
Order By: Relevance
“…LBM relies on a kinetic description which also makes the modelled physics simpler than with Navier-Stokes codes. Indeed, an LBM solver requires less lines of code, which is an asset when it must be adapted to new computing paradigms (for example to GPU [82]). Recent works have also shown that LBM is compatible with an LES framework [83].…”
mentioning
confidence: 99%
“…LBM relies on a kinetic description which also makes the modelled physics simpler than with Navier-Stokes codes. Indeed, an LBM solver requires less lines of code, which is an asset when it must be adapted to new computing paradigms (for example to GPU [82]). Recent works have also shown that LBM is compatible with an LES framework [83].…”
mentioning
confidence: 99%
“…In other work by Brandvik and Pullan [4]; the researchers presented a 3D NS solver on multiple GPUs with MPI. The subroutines for MPI were formulated using Python language.…”
Section: History Of Implementing Gpus On Cfd Applicationsmentioning
confidence: 99%
“…4 shows a schematic of how on the hardware the CUDA program is executed; the programming structure of CUDA is explained in the flowchart inFigure 8.5.…”
mentioning
confidence: 99%
“…These features have motivated a large body of studies, in the area of general purpose computing on GPUs (GPGPU). Recent developments in the use of GPGPU applications in Computational Fluid Dynamics (CFD) [5][6][7][8][9][10][11][12][13] have encouraged us to extend these efforts to the CAA field. The application of GPU computing in CAA field is quite new and there are only a few study cases to the authors' knowledge.…”
Section: Alphanumeric Symbolsmentioning
confidence: 99%